Sustainable Approaches of Ozone Wash and Laser Fading Over Conventional Denim Wash - Md. Nahid-Ull-Islam; Shah Md. Maruf Hasan; Md. Kamrul Hassan Chowdhury; Shahidul Islam Sakib; Sabbir Ahamed; Md. Abu Sayeed; Mahmuda Akter (Tekstilec)
Sustainability is highly valued in the contemporary process of washing denim. The apparel business, specifically the denim washing sector, faces significant sustainability concerns, mostly due to its contribution to water contamination and chemical waste. This study employed a range of strategies to highlight the issue of sustainability in apparel washing. This study examined the sustainability of different denim wash techniques, including ozone wash and ozone wash with laser fading, in comparison with conventional methods. Its aim was to establish the credibility of these techniques as sustainable practices by demonstrating their efficacy across various denim wash categories using environmental impact measurement (EIM) software. Environmental impact measurement evaluates the ecological consequences of apparel across four key areas: water usage, chemical usage, energy consumption during production and the impact on labour. It was observed that the methods mentioned above necessitate minimal usage of water and chemicals, resulting in reduced waste and pollution. This study included a comprehensive assessment of various aspects of apparel washing, and concluded that ozone washing and ozone wash with laser fading are advantageous methods for adopting sustainable washing.